1992
DOI: 10.1093/ije/21.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Are Race Differences in the Prevalence of Hypertension Explained by Body Mass and Fat Distribution? A Survey in a Biracial Population

Abstract: Body mass and body fat distribution are important considerations in the study of hypertension. However, few studies have investigated the relationships with regards to race differences in elevated arterial pressure. A population-based sample of black and white adults was assessed by interview and physical measurement. The prevalence of hypertension (defined as 140/90 mmHg and/or medically treated) was disproportionately higher among blacks than whites. In addition, blacks had a higher prevalence of the more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
3

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 0 publications
6
44
0
3
Order By: Relevance
“…Similar results were observed in the Curaçao Health Study, except that among men the decrease of mean BMI, WHR and WC already set in after the age of 65 y (Grol et al, 1997). Studies among westernised populations show that the prevalence of both overall and central obesity increases with age to about 60-65 y and then declines (Lackland et al, 1992; Obesity in the Netherlands Antilles L Grievink et al Seidell & Visscher, 2000). Compared to Western populations, men as well as women in these three islands of the Netherlands Antilles remain obese until an older age.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were observed in the Curaçao Health Study, except that among men the decrease of mean BMI, WHR and WC already set in after the age of 65 y (Grol et al, 1997). Studies among westernised populations show that the prevalence of both overall and central obesity increases with age to about 60-65 y and then declines (Lackland et al, 1992; Obesity in the Netherlands Antilles L Grievink et al Seidell & Visscher, 2000). Compared to Western populations, men as well as women in these three islands of the Netherlands Antilles remain obese until an older age.…”
Section: Discussionsupporting
confidence: 79%
“…The ®nding that the WHR increases with age is in line with other studies. 11,12 Mean WC among women is much higher than reported in other studies. 11,29 Figure 4 Prevalence of obesity (body mass index (BMI) !…”
Section: Comparisonsmentioning
confidence: 61%
“…Abdominal fatness in Curac Ëao is comparable to that found in a study in a biracial population carried out in the United States. 12 Compared to a study which reports results from four different European countries, the mean WHR among Curac Ëao women is much higher (0.79 vs 0.83). The ®nding that the WHR increases with age is in line with other studies.…”
Section: Comparisonsmentioning
confidence: 68%
See 1 more Smart Citation
“…This is in agreement with previous data where raised blood pressure and an increased prevalence of HT have been observed to be related to both general obesity and fat distribution. 34 External neck circumference is increased in sleep apnoea and it has been suggested that this measurement explains most or all of the link between obesity and sleep apnoea. 35 36 However, when adjusting for neck circumference in our study, DI >10 and lowest desaturation were still independent predictors of HT, indicating that the association between SDB and HT cannot be explained only by an interrelationship with fat distribution.…”
Section: Discussionmentioning
confidence: 99%